Amblyomma americanum serpin 27 (AAS27) is a tick salivary anti-inflammatory protein secreted into the host during feeding. - Lucas Tirloni; Tae Kwon Kim; Markus Berger; Carlos Termignoni; Itabajara da Silva Vaz; Albert Mulenga (Public Library of Science (PLoS), 2019)
Ticks successfully feed and transmit pathogens by injecting pharmacological compounds in saliva to thwart host defenses. We have previously used LC-MS/MS to identify proteins that are present in saliva of unfed Amblyomma americanum ticks that were exposed to different hosts. Here we show that A. americanum serine protease inhibitor (serpin) 27 (AAS27) is an immunogenic saliva protein that is injected into the host within the first day of tick feeding and is an anti-inflammatory protein that might act by blocking plasmin and trypsin functions. Although AAS27 is injected into the host throughout tick feeding, qRT-PCR and western blotting analyses indicate that the respective transcript and protein are present in high amounts within the first 24 h of tick feeding. Biochemical screening of Pichia pastoris-expressed recombinant (r) AAS27 against mammalian proteases related to host defense shows it is an inhibitor of trypsin and plasmin, with stoichiometry of inhibition indices of 3.5 and 3.8, respectively. Consistent with typical inhibitory serpins, rAAS27 formed heat- and SDS-stable irreversible complexes with both proteases. We further demonstrate that rAAS27 inhibits trypsin with ka of 6.46 ± 1.24 x 104 M-1 s-1, comparable to serpins of other tick species. We show that native AAS27 is part of the repertoire of proteins responsible for the inhibitory activity against trypsin in crude tick saliva. AAS27 is likely utilized by the tick to evade the hosts inflammation defense since rAAS27 blocks both formalin and compound 48/80-induced inflammation in rats. Tick immune sera of rabbits that had acquired resistance against tick feeding following repeated infestations with A. americanum or Ixodes scapularis ticks reacts with rAAS27. Of significant interest, antibody to rAAS27 blocks this serpin inhibitory functions. Taken together, we conclude that AAS27 is an anti-inflammatory protein secreted into the host during feeding and may represent a potential candidate for development of an anti-tick vaccine.